Positioning mLearning in formal language learning - Muhammad Ridhuan Tony Lim Abdullah; Saedah Siraj; Lim, Li Yean (Universiti of Malaya Press, 2016)
[This book] offers an alternative viewpoint on how new technology-based approach such as mobile learning (mLearning) should be incorported and structured into mainstream education in augmenting conventional formal learning to aid language learners to achieve their learning goals practically using mobile technologies.